A method of measuring stacked objects volume based on laser sensing. (6th September 2017) - Zhao, Qijie; Wu, Yijing; Li, Xianfa; Xu, Jiao; Meng, Qingxu
Abstract: Stacked objects volume measurement is now widely used in the fields of enterprise material management. It is significant to improve the efficiency of enterprise management and to reduce the cost of management and operation. The method based on laser sensing is one of the key methods to measure the stacked objects volume. This paper presents a laser sensing measurement method of stacked objects based on bottom plane extraction and real-time calibration. A calibration method for a laser scanning sensor and inertial measurement sensor is proposed. Three-dimensional reconstructions of stacked objects and volume calculations are carried out after acquisition and processing of point clouds. Volume measurement experiments of the single box and stacked boxes have been conducted respectively. Experimental results show that the measurement method is feasible and valid with good accuracy.